Cross-linguistic Phonological Transfer: - Jahurul Islam; Md. Sayeed Anwar; Shahriar Mohammad Kamal (Crossings)
The perception and acquisition of non-native tense and lax vowel contrasts have been the subject of extensive research (Bustos et al., 2023; Chang, 2023; Fabra & Romero, 2012; Lai, 2010). Previous studies have highlighted various factors influencing the perception of these contrasts, such as linguistic background, exposure to the target language, and individual phonetic training (Casillas, 2015; Souza et al., 2017; Chang & Weng, 2012). However, there has been limited investigation into whether speakers can transfer discrimination abilities from the vowel contrasts in their first language (L1) to novel contrasts in a second language (L2) that differ in specific phonetic features. Focusing on this inquiry, the present research examines whether native speakers of Bangla, a language with tense/lax contrasts limited to mid vowels, can extrapolate this ability to discriminate tense/lax contrasts among high vowels in English, a language with tense/lax contrasts among both mid and high vowels. Through a forced-choice identification task involving English minimal pairs, data were collected from 43 adult Bangla speakers who had learned L2 English. Contrary to expectations, results indicated that these speakers were unable to effectively distinguish between tense and lax high vowels in English, suggesting that the presence of a similar contrast in L1 does not necessarily facilitate the acquisition of comparable distinctions in L2 across different vowel groups. Implications of the results for non-native vowel acquisition and the pedagogy of English language teaching to Bangla speakers are discussed.